Efficacy of Entomopathogenic Nematodes against Diaphania indica (Saunders) (Lepidoptera:Crambidae) in Bittergourd (Indian Journal of Nematology, 2024)
In vitro experiments were conducted to test the pathogenicity of entomopathogenic nematodes (EPNs) and virulence of infective juveniles (IJs) of effective strain stored in different formulations (sponge, talc and alginate gel) against cucumber moth, Diaphania indica (Saunders) in bitter gourd. Among EPN species tested, Heterorhabditis indica @ 100 IJs recorded the highest mortality (100%) of 3rd instar larvae of D. indica, followed by Steinernema carpocapsae (89.74%) at 48 hrs. H. indica was more virulent with a lower LD50 value (9.54) compared to S. carpocapsae (79.57) at 36 hrs of incubation. IJs of H. indica were stored in different formulations viz., alginate gel, talc, sponge, and water at 27+2°C for 11 weeks, and its pathogenicity was assessed against 3rd instar larvae of D. indica. H. indica IJs stored in talc and alginate formulations for seven weeks showed 68.96 and 75.86% mortality of D. indica larvae, respectively, at 72 hrs. Results of the pot culture study revealed that foliar application of alginate gel and talc-based formulations of H. indica increased mortality of D. indica (75.55 to 77.77%) and reduced leaf damage (41.6 to 51%) significantly in comparison with control and it was found equally effective to bioagent, Beauveria bassiana NBAIR Bb seven days after treatment.